PENDAMPINGAN KOMUNITAS ANAK YATIM DALAM PENINGKATAN POLA HIDUP SEHAT DAN DISIPLIN PADA ERA NEW NORMAL DI PANTI ASUHAN AL-IHSAN DESA DUKUH DEMPOK KECAMATAN WULUHAN KABUPATEN JEMBER - Fajar Abdillah; Anaul Laili (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this assistance is to provide knowledge and skills to orphans so that they adopt a healthy and disciplined lifestyle according to the Covid-19 procedure in the new normal era. The method used is based on Asset Basic Community Development (ABCD). The steps for this method are as follows: 1) Define; Determining the aspects that will be the benchmarks for the mentoring process, 2) Discovery; In-depth discovery, in this case empowerment to carry out an in-depth search process such as finding and detecting 5 assets owned by the community in the al-Ihsan orphanage, 3) Dream; is a step in order to achieve the goals or desires that will be achieved during the ongoing assistance, 4) Design; This process has entered the strategy stage to be used, 5) Deliver; carry out and evaluate all aspects of the deficiencies of implementing a healthy and disciplined lifestyle in the new normal era.